Chad : Third and Fourth Reviews Under the Extended Credit Facility Arrangement, and Requests for Waivers of Nonobservance of Performance Criteria, Augmentation of Access, Extension of the Current Arrangement, and Rephasing of Disbursement-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Chad's Third and Fourth Reviews Under the Extended Credit Facility (ECF) arrangement, and Requests for Waivers of Nonobservance of Performance Criteria (PCs), Augmentation of Access, Extension of the Current Arrangement, and Rephasing of Disbursements. The authorities in Chad have implemented substantial fiscal adjustment to balance the budget and contain the accumulation of arrears. Nonetheless, liquidity conditions remain very tight, and social tensions have risen recently owing to the large cuts in current spending. IMF staff supports the completion of the third and fourth reviews under the ECF arrangement, the waivers of nonobservance of PCs on the nonaccumulation of domestic arrears and nonaccumulation of external arrears.